INTERNET MEME ANALYSIS: INTERPRETIVE SEMIOTIC ANALYSIS ON THE â€œSCUMBAG STEVEâ€ - Ibnu Sulhan (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2016)
In todayâ€™s modern society, communication occurs digitally and wirelessly. A new communication phenomenon has emerged in the past several years. Internet memes, which are defined as a series of cultural items that are being transmitted through the Internet. However, many people do not realize that Internet meme is not just a form of entertainment. In the study, Barthesâ€™ Semiology Theory was used in order to analyze the denotative and connotative meanings of Internet memes; one of them was the â€œScumbag Steve.â€ The researcher also observed them from the mythological perspective, which yielded to findings of this study by interpreting the phenomena of â€œScumbag Steveâ€ and Internet memes as a myth in todayâ€™s society. It appears that the â€œScumbag Steveâ€ and other Internet memes in general are not just forms of entertainment, but rather also used as a means of communication. Keywords: Internet meme, image macro, semiotics, semiology Dewasa ini, komunikasi telah dimudahkan oleh kemajuan teknologi. Dalam beberapa tahun terakhir, muncul suatu fenomena komunikasi baru yaitu Internet meme, yaitu suatu unit dalam perpindahan budaya yang memanfaatkan dunia maya. Saat ini, masih banyak orang yang belum menyadari bahwa meme bukanlah hanya sarana hiburan semata. Teori semiologi dari Roland Barthes dimanfaatkan untuk menganalisis salah satu Internet meme, yaitu karakter â€œScumbag Steve.â€ Peneliti melakukan observasi terhadap makna-makna denotatif dan juga konotatif, serta manambahkan analisis mitos untuk membongkar makna sesungguhnya dari karakter â€œScumbag Steveâ€ dan juga Internet meme secara luas. Hasil dari penelitian menunjukkan bahwa Internet meme bukanlah sekedar wahana hiburan belaka, namun juga merupakan salah satu sarana komunikasi yang efektif. Kata Kunci: Internet meme, image macro, semiotika, semiologi